Privatisation of Security: Private Military Contractors Serving Governments - Jarosław Piątek (Polish Political Science Yearbook, 2017)
Privatisation of security did not appear in the process of revolution. Under conditions of deepening international relations, as well as integration and globalisation processes, security of the state, as well as other entities, is subject to a number of dependencies. The article casts some doubt on how much states are prepared to take such actions, while not losing the attribute of monopoly on violence. Moreover, the article presents doubts about the ranks of modern armed forces. Private Military Firms (PMFs) are new actors the actions of which affect the security. The contemporary image of the PMF functioning is a phenomenon on a global scale. In the twenty-first century, small businesses can have a huge impact on the reality and international affairs. Leaving military firms without state control proves that they do not understand the dynamics, range, risks and challenges posed by cooperation with entities that are allowed to use force. Furthermore, despite devastating consequences that occurred during the state stabilisation operations, these firms continued to outsource services to contractors, while not creating any legal control over them.